PENGARUH KECEPATAN PUTAR SPINDLE (RPM) DAN JENIS SUDUT PAHAT PADA PROSES PEMBUBUTAN TERHADAP TINGKAT KEKASARAN BENDA KERJA BAJA EMS 45 - Farokhi, Mohammad; Sumbodo, Wirawan; Rusiyanto, Rusiyanto (Sainteknol : Jurnal Sains dan Teknologi, 2017)
The purpose of this research to know the influence of kecepatanm turn spindle ( rpm ) and angles chisel on the level of roughness pembubutan carbon steel ems 45. This research in a research experiment , with objective of knowing the and effect based on treatment given .Variation speed spindle used the 2000 rpm , 2250 rpm , 2500 rpm , 2750 rpm , and 3000 rpm. While angles chisel in variasikan that is, an angle 35º, angles 55º, and angles 80 º. After conducted lathe next tested value roughness. An analysis of the data used to research these are the statistics descriptive. The results of the analysis data on the research indicated that the more the acute angle chisel this value surface roughness the lower.